Turbulence in the near-Venusian space: Venus Express observations - SuDong Xiao; MingYu Wu; GuoQiang Wang; Geng Wang; YuanQiang Chen; TieLong Zhang (Earth and Planetary Physics, 2020)
With Venus Express magnetic field measurements at 32 Hz from 2006 to 2012, we investigate statistically the magnetic fluctuations in the near-Venusian space. The global spatial distribution of their spectral scaling features is presented in MHD and kinetic regimes. It can be observed that turbulence is a common phenomenon in the solar wind in both regimes. The solar wind MHD turbulence is modified at the Venusian bow shock; MHD turbulence is absent in the Venusian magnetosheath but present at the magnetosheath boundary layer. Pre-existing kinetic turbulence from the far upstream solar wind is modified in the near solar wind region, while kinetic turbulence can be extensively observed throughout the Venusian magnetosheath and in some regions of the induced magnetosphere. Our results reveal that, in the near-Venusian space, energy cascade can be developed at the boundary between magnetosheath and wake, and the turbulence-related dissipation of magnetic energy occurs extensively in the magnetosheath and the induced magnetosphere.